Telling the cruelty – an analysis of nonverbal behaviours of war crimes witnesses - Liber-Kwiecińska, Katarzyna (Papers in Linguistics, 2023)
The study focused on nonverbal behaviours of witnesses to war crimes accompanying their verbalization of traumatic memories. The undertaken analysis involved fifty-five testimonies given by witnesses of crimes committed in Bosnia and Herzegovina in the period 1991–1995, as well as testimonies in documentary films about the civil war in the former Yugoslavia. The purpose of the study was to determine in which parts of the testimony the witnesses’ gestures are most intense, and to isolate the main categories of gestural behaviour exhibited by the victims of war crimes in order to visualize their experiences for the audience and clarify the verbal message. Taking into consideration the findings in the field of trauma psychology, it assumed that in the case of war crimes testimonies gestures may be a direct translation of coded images and impressions deprived of a linear narrative, and they may actively support the verbalization of traumatic experiences that victims find difficult to put into words. The article discusses the categories of gestures identified during the analysis, which are accompanied by photographic material from selected testimonies.